2008
DOI: 10.1193/1.2924363
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the NGA Ground-Motion Relations

Abstract: The data sets, model parameterizations, and results from the five NGA models for shallow crustal earthquakes in active tectonic regions are compared. A key difference in the data sets is the inclusion or exclusion of aftershocks. A comparison of the median spectral values for strike-slip earthquakes shows that they are within a factor of 1.5 for magnitudes between 6.0 and 7.0 for distances less than 100 km. The differences increase to a factor of 2 for M5 and M8 earthquakes, for buried ruptures, and for distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(146 citation statements)
references
References 8 publications
6
137
2
1
Order By: Relevance
“…Abrahamson et al 2008). This further confirms the importance of modelling complex wave propagation phenomena such as scattering in the near source region even at intermediate frequency.…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 66%
See 1 more Smart Citation
“…Abrahamson et al 2008). This further confirms the importance of modelling complex wave propagation phenomena such as scattering in the near source region even at intermediate frequency.…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 66%
“…By comparison, standard deviation from empirical ground-motion prediction equations at 30 km on rock soils (Abrahamson et al 2008). It is therefore important to consider the combined effect on ground-motion variability of both topography and velocity heterogeneity.…”
Section: Ground-motion Variabilitymentioning
confidence: 99%
“…Finally, the layout in which points are arranged in clusters is considered. Figure 12 shows examples of 9-site layouts arranged into three three-site clusters centered at coordinates (0,0), (50,50) and (25,75). For each cluster, points are equally distributed around a circle of radius .…”
Section: Resultsmentioning
confidence: 99%
“…Readers familiar with seismic applications will recognize (17) as the general formulation of a ground-motion prediction equation (also known as an attenuation relation), see, e.g. [25].…”
Section: Effect Of Correlation Approximations On System Reliabilitymentioning
confidence: 99%
“…The recent set of NGA GMPEs (e.g. Abrahamson et al, 2008) do use some data from EMME but the models are not highly dependent on these data. Stafford et al (2008) quantitatively examine, using an extended Scherbaum et al (2004) technique, the ability of one of the NGA models to predict observed ground motions in EMME.…”
Section: Evidence From Strong-motion Datamentioning
confidence: 99%